Effect of dietary tryptophan supplementation on growth, body composition and digestive enzymes activity of juvenile silver pompano Trachinotus blochii (Lacepede, 1801) - Devassykutty, Meenu; Ignatius, Boby; P, Vijayagopal; Ebeneezar, Sanal; Sawant, Paramita; A. M., Babitha rani; Varghese, Eldho; P, Sayooj; K.A, Sajina (Indian Journal of Fisheries, 2022)
A 60-day feeding trial was conducted to study the effect of dietary supplementation of tryptophan in juvenile silver pompanoTrachinotus blochii (Lacepede, 1801) (Average initial weight=6.81±0.05 g). Five isonitrogenous and isolipidic feedssupplemented with tryptophan at different levels, 0 (TRP0), 0.5 (TRP0.5), 1.0 (TRP1.0), 1.5 (TRP1.5) and 2.0 (TRP2.0) g 100 g-1of diets were formulated. The weight gain%, specific growth rate, hepato-somatic index, digestives enzymes of stomach andintestine except protease activity in stomach, red blood cells, white blood cells, crude protein, fat and ash content of the fishwere significantly influenced (p